Mechanistic study and performance evaluation of steam assisted gravity drainage using direct visualisation of pore-level experiments. (30th April 2020) - Mohammadzadeh, Omid; Rezaei, Nima; Chatzis, Ioannis
In this paper, insights into the pore-scale physics of SAGD process are presented through analysis of a systematic series of SAGD visualisation experiments, conducted using optical imaging technique and glass-etched micromodels of capillary networks. The steam chamber propagation was found to be influenced by the randomly-distributed fingering of the invading steam front near the mobile oil-steam chamber interface. The steam fingering was extensive during the vertical growth of the steam chamber where the steam buoyant front was protruding through the pores containing a continuum of oil. The steam fingering phenomenon was also observed during the outward propagation of the steam chamber near its lateral wings, but to a lesser extent. The rate of pore-scale horizontal interface advancement was constant at each elevation along the height of the micromodels. The average pore-level SAGD sweep rates as well as the net cumulative steam to oil ratio were correlated using an analytical model. [Received: March 15, 2018; Accepted: February 11, 2019]